White matter connections of the inferior parietal lobule: A study of surgical anatomy. Issue 4 (8th March 2017) - Burks, Joshua D.; Boettcher, Lillian B.; Conner, Andrew K.; Glenn, Chad A.; Bonney, Phillip A.; Baker, Cordell M.; Briggs, Robert G.; Pittman, Nathan A.; O'Donoghue, Daniel L.; Wu, Dee H.; Sughrue, Michael E.
Abstract: Introduction: Interest in the function of the inferior parietal lobule (IPL) has resulted in increased understanding of its involvement in visuospatial and cognitive functioning, and its role in semantic networks. A basic understanding of the nuanced white‐matter anatomy in this region may be useful in improving outcomes when operating in this region of the brain. We sought to derive the surgical relationship between the IPL and underlying major white‐matter bundles by characterizing macroscopic connectivity. Methods: Data of 10 healthy adult controls from the Human Connectome Project were used for tractography analysis. All IPL connections were mapped in both hemispheres, and distances were recorded between cortical landmarks and major tracts. Ten postmortem dissections were then performed using a modified Klingler technique to serve as ground truth. Results: We identified three major types of connections of the IPL. (1) Short association fibers connect the supramarginal and angular gyri, and connect both of these gyri to the superior parietal lobule. (2) Fiber bundles from the IPL connect to the frontal lobe by joining the superior longitudinal fasciculus near the termination of the Sylvian fissure. (3) Fiber bundles from the IPL connect to the temporal lobe by joining the middle longitudinal fasciculus just inferior to the margin of the superior temporal sulcus. Conclusions: We present a summary of the relevant anatomy of the IPL as part of a larger effort to understand the anatomic connections of related networks. This study highlights the principle white‐matter pathways and highlights key underlying connections. Abstract : A basic understanding of the nuanced white‐matter anatomy of the inferior parietal lobule may be useful to preserving the semantic network when operating in this region of the brain. We identified three major types of connections in this region. This study highlights the principle white‐matter pathways and highlights key underlying connections.